SENSLOPE v.3 development and evaluation of alternative cost-effective instrumentation for monitoring landslides on real world slopes - Carreon, Catherine Ruffa C. (2011)
Landslide monitoring is of utmost importance in the Philippines as seen in the Guinsaugon and Little Kinungan disasters. In June 2008, the Disaster Risk Management using Sensors, Network and Computing (DRMS) research program was started. Among the program's objectives are to develop low cost landslide monitoring instruments and to model the dynamic behavior of landslides. The program is a collaboration between the Department of Science and Technology (DOST), UP National Institute of Geological Sciences (NIGS), UP Institute of Civil Engineering (ICE), and UP Electrical and Electronics Engineering Institute (EEEI). It is divided into two component projects, Senslope and Dynaslope. In this work, we discuss the latest developments in the Senslope project. The first phase of Senslope focused on the development of a laboratory scale prototype instrumentation system which measures slope movement, soil moisture, and pore water pressure. The second phase developed the controller area network (CAN) bootloader for field programmability, the accelerometer-based ground shaking sensor, and the graphical user interface (GUI). Further characterization of the soil moisture sensor was also performed in the second phase. In its third phase, we focused on developing a low-cost landslide monitoring system for field deployment. The instruments employed were a sensor column array composed of tilt and soil moisture sensors and a vibrating-wire piezometer, both controlled by PIC microcontrollers. Improvements on the CAN scheduling algorithm of the sensors were implemented to replace the old daisy-chain implementation. On-site logging was done in a Secure Data (SD) Card and a GSM/GPRS connection was used in transmitting the data to a remote base station. The current system is AC powered but an off-grid photovoltaic power system was also developed which can be implemented in far-flung areas where power from the grid might not be available. The photovoltaic system has a maximum power point tracking (MPPT) charge controller to extract more power from the solar panel. Dynamic tuning of sensor sampling rate was implemented to save power which is being triggered by vibration measurements of a ground shaking node. Several chemical and field tests were done on the sensor nodes in order to test its durability. An electrofusion coupler was used to connect the sensor nodes and more water proofing and strength tests were done on the sensor column packaging. The system was successfully deployed in Little Kibungan, Benguet with the data made available to geologists and geotechnical engineers for soil dynamics study.